Mathematical Aspects of Computer and Information Sciences: 6th International Conference, MACIS 2015, Berlin, Germany, November 11-13, 2015, Revised Selected Papers - Kotsireas, Ilias S.; Rump, Siegfried M.; Yap, Chee K. (Lecture notes in computer science, 2016)
This book constitutes the thoroughly refereed post-conference proceedings of the 6th International Conference on Mathematical Aspects of Computer and Information Sciences, MACIS 2015, held in Berlin, Germany, in November 2015. The 48 revised papers presented together with 7 invited papers were carefully reviewed and selected from numerous submissions. The papers are grouped in topical sections on curves and surfaces, applied algebraic geometry, cryptography, verified numerical computation, polynomial system solving, managing massive data, computational theory of differential and difference equations, data and knowledge exploration, algorithm engineering in geometric computing, real complexity: theory and practice, global optimization, and general session